Capital markets and EMU : report of a CEPS Working Party - Padoa-Schioppa, Tommaso; Centre for European Policy Studies (CEPS) (Brussels : CEPS, 1998)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: financieel beleid; Europese Unie (EU).